Designing healthy communities - Jackson, Richard, 1945- (Jossey-Bass, 2012)
"Designing Healthy Communities is Dr. Richard J. Jackson's call to action for all of us concerned with the health trends that are beginning to overwhelm the country. It is a companion book for the upcoming special PBS broadcast that describes how the design of the built environment impacts our health, with an additional emphasis on the inequities of social and environmental justice. In this book, Dr. Jackson explores how the built environment has contributed to the fact that two-thirds of Americans are overweight, 70 million are obese and many suffer from an array of other chronic but preventable diseases. The book and series looks upstream at the root causes of our malaise, and highlights actionable best practices based on real people with real solutions. Public health has traditionally associated the built environment with issues such as poor sanitation, lead paint poisoning and children, workplace safety, fire codes and access for persons with disabilities. We now realize that how we design the built environment may hold tremendous potential for addressing---and hopefully preventing---many of the nation's current public health concerns. The Designing Healthy Communities book offers a new perspective on the topics covered in each episode while providing a roadmap and tools for readers to effect similar positive change in their own communities. Dr. Jackson is a vibrant public speaker, highly skilled at distilling ideas to a simple and understandable conversation. Unlike textbooks on the topic, this book seeks to feel more like a conversation between Dr. Jackson and the many people he has met along the road. Through stories and examples, he will encourage readers to consider their own experience and why taking initiative to make positive change in society is important. Part 1 - Living and Leading With Purpose: Introduces the major themes that guide Dick Jackson's life and work. This section sets the stage and provides a context for understanding specific actions. In each thematic area, we move from the specific (ourselves and those close to us) to the broader view.Chapter 1: What Does Caritas Have to Do With the Built Environment?Chapter 2: What is Health and How Do We Measure It? Chapter 3: Can Built Environment Build CommunityPart 2 - A Legacy in Concrete: Each chapter details a place where Dick Jackson's ideas have been manifested. Each chapter reviews the community in the style of a medical case study: symptoms, diagnosis, cure, and prevention. This is the nuts-and-bolts of Dr. Jackson's view of public health is manifested in specific locations.Chapter 4: From Monoculture to Human Culture - curing social and environmental malnutrition: Belmar, ColoradoChapter 5: Using the Principles of New Urbanism to Build Community Prairie Crossing, IllinoisChapter 6: Saving America's downtown and local history through the political process: Charleston, South CarolinaChapter 7: Reinventing a City through Community Leadership for Sustainability: a vital part of sustainability is being healthy: Elgin, IllinoisChapter 8: Ending Car Captivity - Leadership Paths to Culture: Boulder, ColoradoChapter 9: Ports Are Rest Stops Along the Global Highway: Oakland, CaliforniaChapter 10: The city that won't give up - entrepreneurship and urban agriculture: Detroit, MichiganPart 3 - Be The Change You Want to See in the World: This section makes the case that the reader can use Dick Jackson's vision and tools to effect similar improvements in their own communities. Chapters examine how to effect change through the power of one person leading groups with purpose and working effectively to engage others. We introduce the different stakeholders in a community (government agencies, NGOs, parents, children, businesses, professionals, etc.) and discuss how they work together to achieve results.Chapter 11: What's Happening in Your Community?Chapter 12: Who Are the Players?Chapter 13: Create an Action PlanEpilogue: You are Dick Jackson"--